Looking south : race, gender, and the transformation of labor from reconstruction to globalization - Frederickson, Mary E. (Southern dissent., 2011)
In the United States, cheap products made by cheap labor are in especially high demand, purchased by men and women who have watched their own wages decline and jobs disappear. 'Looking South' examines the effects of race, class, and gender in the development of the low-wage, anti-union, and state-supported industries that marked the creation of the New South and now the Global South.